NIKOLA TESLA AND THE X-RAY HARMFULNESS - Rade R. Babić (Acta Medica Medianae, 2005)
Nikola Tesla was the first scientist to point out that the x-ray could damage a live cell. He carefully noted the visible effects of the x-ray on human body and explained its harmful activity on the live cell. Therefore, he tried to find some means of protection from the x-ray harmfulness. He suggested to set an aluminium board between the person irradiated and the x-ray tube for the sake of protection. He also indicated the importance of law application.